2005
DOI: 10.1038/ja.2005.53
|View full text |Cite
|
Sign up to set email alerts
|

Aurovertin E, a New Polyene Pyrone from the Basidiomycete Albatrellus confluens

Abstract: A new polyene pyrone, aurovertin E (2), was isolated along with aurovertin B (1) from the culture mycelia of the basidiomycete Albatrellus confluens. Their structures were elucidated on the basis of spectroscopic studies including 2D NMR experiments. This is the first example of the occurrence of aurovertins in basidiomycetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 14 publications
(9 reference statements)
0
45
0
Order By: Relevance
“…[5][6][7] China is extraordinarily rich in higher fungi, with over 6000 species reported to belong to about 1200 genera. In our on-going research to explore the biologically active natural products of the higher fungi of China, [8][9][10][11][12] the chemical constituents of the fruiting bodies of Lactarius vellereus were investigated. This report describes the isolation and structure elucidation of an unusual highly functionalized lactarane sesquiterpene, named velleratretraol (1), and its anti-HIV activity.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] China is extraordinarily rich in higher fungi, with over 6000 species reported to belong to about 1200 genera. In our on-going research to explore the biologically active natural products of the higher fungi of China, [8][9][10][11][12] the chemical constituents of the fruiting bodies of Lactarius vellereus were investigated. This report describes the isolation and structure elucidation of an unusual highly functionalized lactarane sesquiterpene, named velleratretraol (1), and its anti-HIV activity.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular formula C 23 H 32 O 8 was determined by HREIMS at m/z 436.2097 [M] + . The 1D and 2D NMR data suggested that the structure of 5 was related to that of aurovertin E (13), 8 except that the double bond between C-9 and C-10 in 14 was opened to form a hydroxymethine at C-10 (δ C 69.8), as implied by the HMBC correlations from δ H 4.53 (1H, br. s, H-10) to δ C 75.9 (d, C-8), 39.6 (t, C-9), and 141.5 (d, C-11).…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the known compounds 11-14 isolated were identified as aurovertin B, 5 aurovertin C, 22 aurovertin E, 8 and aurovertin I, 10 respectively, by comparison of their spectroscopic data with literature values. All aurovertins obtained from cultures of the basidiomycete A. confluens were yellow syrup, and could not obtain as crystals in diverse solution systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations